Possíveis efeitos do trabalho sexual na saúde mental de travestis e mulheres transexuais - Stefaniszen, Victor (Universidade Federal de São Carlos, 2025)
Various cultures have recognized gender identities beyond the male/female binary. European thought marginalized these existences, imposing rigid gender and sexuality norms based on anatomical characteristics. In Brazil, travestis and, later, transsexuals underwent processes of subalternization, with knowledge systems condemning or pathologizing their experiences. Despite this, social movements have enabled advances in rights. Psychiatry, Psychology, and Psychoanalysis contributed to the pathologization of these identities by creating diagnoses for these groups. Similarly, the body of the prostitute was treated as an object of medical interest, opposed to an ideal of normality. Today, there are critiques of these approaches and efforts to understand the social determinants of health for these populations. This study aims to understand the possible impacts of sex work on the mental health of transsexual women and travestis. To this end, five semi-structured interviews were conducted with travestis and transsexual women engaged in sex work in Sorocaba. The analysis was based on repeated readings, interpretation of the narratives, identification of recurring information, and thematic categorization. The testimonies were compared with previously published academic literature on the subject. The results indicate significant impacts on their mental health, such as fears, anxieties, and the development of psychological defenses to cope with sex work. They also described physical and psychological symptoms, substance abuse, feelings of loneliness, and difficulties integrating into the formal labor market. However, they reported positive aspects, such as support networks among sex workers and creative strategies to face the dangers of the profession. Participants also criticized the role of government and NGOs in promoting the mental health of this group, suggesting the need for more effective strategies and more humane support. It is concluded that further research is needed to deepen the understanding of this topic.
Possible effects of sex work on the mental health of travestis and transgender women
Keywords: Saúde Mental; Trabalho Sexual; Travestis; Transexuais; Mental Health; Sex Work; Transgender; CIENCIAS HUMANAS; CIENCIAS HUMANAS::PSICOLOGIA